The vision of medical school teachers of a higher education institution in Palmas - Tocantins on telemedicine (Research, Society and Development, 2021)
Telemedicine is an instrument that uses communication technology and makes it possible to provide access to health, solving problems in which distance would be a critical factor. Objective: To know the view of the professors of the medical course of a higher education institution in Palmas – Tocantins about telemedicine. Methodology: cross-sectional and descriptive research, with a quantitative and qualitative approach, developed with medical school professors from the 1st to the 8th period of Instituto Tocantinense Presidente Antônio Carlos – ITPAC Palmas. Data were collected from May to September, through an online questionnaire made available through GoogleForms® in order to analyze the view of the HEI professors on the growth and diffusion of telemedicine, containing 21 questions that addressed this theme. Results: 34.6% of the sample disbelieve in the full guarantee of safety/secrecy to the patient during remote care, and that consultations using telemedicine do not replace face-to-face follow-up, as many medical specialties lack the face-to-face doctor-patient relationship to achieve success in health care. It is noteworthy that the positive points were also identified, such as: greater reach to the population, possibility of contact between specialists and relief from the burden of the Unified Health System. Conclusion: The view of the professors regarding the use of telemedicine is multifaceted. It has negative points such as the difficulty of attending some specialties, and positive points such as: expanding access and sharing of knowledge among professionals. The expansion of studies and debates involving the subject is suggested.